Poverty, Place, and Rurality: Material and Sociocultural Disconnections. (March 2014) - Milbourne, Paul
Recent academic critiques of poverty have pointed to the need to pay more attention to the relations between the material, social, and cultural dimensions of poverty as well as to the lived worlds of those on low income. This paper addresses these themes by exploring the ways in which people living in situations of material poverty discuss their everyday lives. Drawing on survey and interview materials from a recent study of poverty in rural Wales, the paper illustrates how people on low income construct their lives more in relation to their social and cultural worlds than to issues of low income and material deprivation. Key findings from the study reveal important disconnections between material and sociocultural aspects of rural poverty, with community belonging and attachment to landscape appearing more significant than material hardship and social exclusion within poor people's narratives of their everyday lives. Community belonging is also bound up with particular moral discourses of welfare and rurality that act to perpetuate situations of material poverty within rural places.